الآثار البيئية والاقتصادية لتدهور الموارد المائية في مزارع ضواحي مدينة الزاوية خلال الفترة (2000-2024م) (Comprehensive Journal of Science, 2026)
Objective: This study aims to monitor and analyze the repercussions of the qualitative and quantitative degradation of groundwater resources in the suburbs of Al-Zawiya (Juda'im, Al-Harsha, Abu Sarah, and Al-Matrad). It investigates the link between water deterioration and environmental changes in soil and vegetation, while measuring the resulting economic losses and farmers' adaptation capacities.Methodology: The study adopted an integrated analytical and inductive methodology, incorporating modern geospatial techniques and field research, including:Hydrochemical Analysis: Collecting and analyzing samples from 40 groundwater wells to measure salinity indicators (TDS) and chloride concentrations.Geospatial Techniques: Utilizing Geographic Information Systems (GIS) to model the spatial extent of seawater intrusion and Remote Sensing (NDVI) to assess salt-induced stress on vegetation.Theoretical Framework: Applying the "Ecological Equilibrium Theory" and the "Tragedy of the Commons" to interpret human behavior toward water resources.Key Findings:Severe Qualitative Degradation: The study recorded a significant advancement of the "saltwater wedge" (seawater intrusion) at distances ranging from 1.5 to 3 km inland, with groundwater salinity (TDS) increasing by over 370% compared to the year 2000.Environmental Collapse: Irrigation with highly saline water led to "soil salinization" and the collapse of its physical structure, resulting in the death of perennial trees and the drying up of cash crops (citrus and almond trees).Economic Depletion: Agricultural production costs rose by 200% due to the need for deeper wells and private desalination units, leading to a 45% decline in net profit margins.Urban Sprawl Catalyst: The study confirmed that water degradation acted as the primary "economic driver" pushing farmers to abandon agriculture and transform their farms into unplanned residential plots, directly linking these findings to the urban sprawl phenomenon observed in the region.Recommendations:Declare "Water Protection Zones" in coastal suburbs to prohibit drilling new wells and protect the coastal aquifer.Expand the use of treated wastewater for irrigating green belts to alleviate pressure on groundwater.Provide technical and financial support for farmers to transition toward smart irrigation systems and cultivate salt-tolerant crop varieties to ensure agricultural sustainability.
Keywords: Seawater intrusion, Hydrological degradation, Soil salinization, Economic adaptation, Al-Zawiya City, Environmental sustainability